2000
DOI: 10.1034/j.1600-0625.2000.009006401.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of endothelin‐1 in normal human keratinocytes by UVA1/B radiations, prostaglandin E2 and peptidase inhibitors

Abstract: In the skin, keratinocytes synthesize and secrete endothelin-(ET-1), a potent vasoconstrictor peptide which acts also as a growth factor for most skin cells. The aim of the study was to test the effects of UVA1 and the associations UVA1/B on the expression of ET-1 in normal human keratinocytes and to determine whether exogenously added prostaglandin E2 (PGE2) regulated ET-1 expression. As ET-1 is susceptible to degradation, we also evaluated whether ET-1 secretion was modulated by peptidase inhibitors. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
2
11
1
2
Order By: Relevance
“…In contrast, UVB led to an increase of bFGF and ET‐1, but did not alter the production of the other growth factors. The reduction of ET‐1 protein by UVA in contrast to the upregulation of ET‐1 protein by UVB is in accordance with previous reports 23,26 , 27 . However, Pernet et al 26 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, UVB led to an increase of bFGF and ET‐1, but did not alter the production of the other growth factors. The reduction of ET‐1 protein by UVA in contrast to the upregulation of ET‐1 protein by UVB is in accordance with previous reports 23,26 , 27 . However, Pernet et al 26 .…”
Section: Discussionsupporting
confidence: 92%
“…The reduction of ET-1 protein by UVA in contrast to the upregulation of ET-1 protein by UVB is in accordance with previous reports. 23,26,27 However, Pernet et al 26 while we observed a marked increase in ET-1 mRNA expression by UVB and a slight increase by UVA 12 h after irradiation. This discrepancy between the UVA-induced increase in ET-1 mRNA, but decrease in ET-1 protein, suggests that UVA may have inhibited ET-1 at the post-transcriptional level, for example by suppressing the secretion of protein.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Confirming recent in vitro data and findings in the skin of human and mouse skin that expression and release of ET-1 is markedly enhanced in response to UVB, 9,16,25,29 we show that ET-1 concentrations in UVB-irradiated skin increase more than 13-fold above baseline levels. This UV-mediated increase in ET-1 levels is associated with augmented skin inflammation resulting, in part, from MCs activated by 4 These differences reflect the ability of MCs to either promote homeostasis and, thus, to diminish pathology (eg, by degrading endogenous or exogenous toxins through the release of proteases) 4 or to induce pathology (eg, by releasing potent proinflammatory mediators such as tumor necrosis factor-␣, histamine, leukotrienes, and many more).…”
Section: Discussionsupporting
confidence: 74%
“…10 Other compounds may be also utilized to affect the ET-1 autocrine loop by reducing ET-1 synthesis, such as inhibitors of ET-1 converting enzyme. 11 In conclusion, we have shown some indications for the development of new therapeutic strategies in psoriatic patients by altering the biological response of keratinocytes to the ET-1 proliferative stimuli. These new therapies would not affect the pathological causes of this skin disorder but could reduce and stabilize the symptoms that are the major problem of patients with this disease.…”
mentioning
confidence: 84%